Active membrane recycling induced morphology changes in vesicles - Sachin Krishnan, T. V.; Sunil Kumar, P. B. (Frontiers in Physics, 2022)
Membranes of organelles in the intracellular trafficking pathway continuously undergo recycling through fission and fusion processes. The effect of these recycling processes on the large-scale morphology of organelles is not well understood. Using a dynamically triangulated surface model, we developed a membrane morphology simulator that allows for membrane trafficking, and analyzed the steady state shape of vesicles subjected to such active remodeling. We study a two-component vesicle composed of 1) active species which can have nonzero spontaneous curvature and participate in the recycling and 2) inactive species which do not participate in the recycling. We obtain a plethora of steady state morphologies as a function of the activity rate, spontaneous curvature, and the strength of interaction between species. We observe that morphology changes, as a function of rate of activity, are diametrically opposite for the two signs of the spontaneous curvature, but only have a weak effect on its magnitude. The interplay between the in-plane diffusion, the activity rate, and the spontaneous curvature are shown to determine the vesicle morphology at the steady state. It is shown that the spontaneous curvature and activity inhibits the formation of clusters of active species on the surface. We carry out linear stability analysis of a continuum model and show that the spherical shape of a vesicle is indeed unstable when subjected to active membrane recycling above a certain activity rate.